2021
DOI: 10.6017/ital.v40i1.12453
|View full text |Cite
|
Sign up to set email alerts
|

Web Content Strategy in Practice within Academic Libraries

Abstract: Web content strategy is a relatively new area of practice in industry, in higher education, and, correspondingly, within academic and research libraries. The authors conducted a web-based survey of academic and research library professionals in order to identify present trends in this area of professional practice by academic librarians and to establish an understanding of the degree of institutional engagement in web content strategy within academic and research libraries. This article presents the findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As previously defined, content strategy is "the practice of planning for the creation, delivery, and governance of useful, usable content." 5 Content strategy is "the practice of planning for the creation, delivery, and governance of useful, usable content. "…”
Section: Web Content Strategy and Its Practice In Librariesmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously defined, content strategy is "the practice of planning for the creation, delivery, and governance of useful, usable content." 5 Content strategy is "the practice of planning for the creation, delivery, and governance of useful, usable content. "…”
Section: Web Content Strategy and Its Practice In Librariesmentioning
confidence: 99%
“…These responses align broadly with findings from the previously mentioned 2021 research paper indicating "higher levels of maturity in the elements of planning, creation and UX, and lower levels in the elements of delivery and governance." 30 Finally, participants were asked to self-assess the content strategy maturity of their organization, with four responses each for "basic" and "intermediate" and one response of "advanced. "…”
Section: Content Strategy Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have explored content management at the institutional level. Notably, McDonald and Burkhardt (2021) summarized findings from a survey of content managers at academic libraries and found that "web content strategy as a community of practice in academic libraries is operating at, or just above, a basic level" (p.15). This is similar to Logan and Spence's findings.…”
Section: Commentarymentioning
confidence: 99%